(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2023)
This article analyzes the ongoing reforms in our country to improve the standard of living of the population, and shows indicators of it. The article also provides suggestions and recommendations for further improving the standard of living of the population.